2011
DOI: 10.1111/j.1601-5037.2011.00522.x
|View full text |Cite
|
Sign up to set email alerts
|

The comparative evaluation of the effects of tongue cleaning on salivary levels of mutans streptococci in children

Abstract: The results of the present study show that tongue scraping and tongue brushing demonstrated statistically significant reductions in salivary mutans streptococci counts after 10 days and also after 21 days. It was also noted that tongue scraping and tongue brushing were equally effective in reducing colony counts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 17 publications
1
6
0
1
Order By: Relevance
“…16 Rupesh et al, (2011) evaluated the effects of tongue cleaning in mutans streptococci levels and reported significant reductions in 10 days and after 21 days. 17 The observations from these studies support the reduction in plaque scores demonstrated by tongue cleaning in the present study.…”
Section: Discussionsupporting
confidence: 88%
“…16 Rupesh et al, (2011) evaluated the effects of tongue cleaning in mutans streptococci levels and reported significant reductions in 10 days and after 21 days. 17 The observations from these studies support the reduction in plaque scores demonstrated by tongue cleaning in the present study.…”
Section: Discussionsupporting
confidence: 88%
“…compared and evaluated the effects of tongue scraping and tongue brushing on salivary MS levels in children. [ 19 ] There had been statistically significant reduction after 10 days and 21 days. It was observed that both tongue scraping and tongue brushing were equally effective.…”
Section: Discussionmentioning
confidence: 99%
“…TB removal is necessary to reduce the incidence of nosocomial pneumonia (1) and halitosis. TB removal is an easy and effective oral hygiene method, (7,16) which can improve the motor function of the tongue. (17) This study found a high rate of culture positivity in the oral and tracheal secretions from the SG even after the TB was removed.…”
Section: Discussionmentioning
confidence: 99%